Next Article in Journal
On the Fekete–Szegö Type Functionals for Close-to-Convex Functions
Next Article in Special Issue
Properties of Partially Degenerate Complex Appell Polynomials
Previous Article in Journal
The Influence of AlGaN/GaN Heteroepitaxial Structure Fractal Geometry on Size Effects in Microwave Characteristics of AlGaN/GaN HEMTs
Previous Article in Special Issue
Identities Involving the Fourth-Order Linear Recurrence Sequence

Font Type:
Arial Georgia Verdana
Font Size:
Aa Aa Aa
Line Spacing:
Column Width:
Background:
Article

# Some New Identities of Second Order Linear Recurrence Sequences

by
Yanyan Liu
1 and
Xingxing Lv
2,*
1
School of Education, Xizang Minzu University, Xianyang 712082, China
2
School of Mathematics, Northwest University, Xi’an 710127, China
*
Author to whom correspondence should be addressed.
Symmetry 2019, 11(12), 1496; https://doi.org/10.3390/sym11121496
Submission received: 21 November 2019 / Revised: 4 December 2019 / Accepted: 5 December 2019 / Published: 10 December 2019

## Abstract

:
The main purpose of this paper is using the combinatorial method, the properties of the power series and characteristic roots to study the computational problem of the symmetric sums of a certain second-order linear recurrence sequences, and obtain some new and interesting identities. These results not only improve on some of the existing results, but are also simpler and more beautiful. Of course, these identities profoundly reveal the regularity of the second-order linear recursive sequence, which can greatly facilitate the calculation of the symmetric sums of the sequences in practice.
MSC:
11B83

## 1. Introduction

The defined of second-order linear recurrence sequence ${ S n }$ is
where n is integers with $n ≥ 0$.
For convenience, we also extend the recursive property of $S n$ to all negative integers.
We taking $C 1 = x$, $C 2 = 1$, $S n = F n + 1 ( x )$ with $F 0 ( x ) = 0$, $F 1 ( x ) = 1$ in (1), then ${ S n }$ becomes the famous Fibonacci polynomial sequence ${ F n + 1 ( x ) }$. That is,
Especially when $x = 1$, $F n ( 1 ) = F n$ becomes known as the Fibonacci sequence.
Let $α = x + x 2 + 4 2$ and $β = x − x 2 + 4 2$ denote the two roots of the characteristic equation $λ 2 − x λ − 1 = 0$. Then we have
$F n ( x ) = α n − β n α − β , L n ( x ) = α n + β n , n = 0 , 1 , 2 , ⋯ ,$
where $L n ( x )$ denotes the Lucas polynomials, and $L n ( 1 )$ denotes the Lucas sequence.
If we take $C 1 = 2 x$, $C 2 = − 1$ in (1), then $S n = U n ( x )$ is Chebyshov polynomials of the second kind with $U 0 ( x ) = 1$ and $U 1 ( x ) = 2 x$. Chebyshov polynomials $T n ( x )$ of the first kind is defined by $T n + 2 ( x ) = 2 x T n + 1 ( x ) − T n ( x )$ for all $n ≥ 0$ with $T 0 ( x ) = 1$ and $T 1 ( x ) = x$. Let $δ = x + x 2 − 1$, $γ = x − x 2 − 1$ are two characteristic roots of the polynomial $λ 2 − 2 x λ + 1 = 0$, then (see [1])
$T n ( x ) = 1 2 δ n + γ n , U n ( x ) = δ n + 1 − γ n + 1 δ − γ , n = 0 , 1 , 2 , ⋯ .$
Many scholars have studied $S n$, and obtained a series of valuable research results. For example, Yi Yuan and Zhang Wenpeng [2] proved the following conclusion: For any positive integer n and k, one has the identity
$∑ a 1 + a 2 + ⋯ + a k = n F a 1 ( x ) · F a 2 ( x ) · F a 3 ( x ) ⋯ F a k ( x ) = ∑ m = 0 n 2 n + k − 1 − m m n + k − 1 − 2 m k − 1 · x n − 2 m ,$
where $∑ a 1 + a 2 + ⋯ + a k = n$ denotes the summation is taken over all k-dimension nonnegative integer coordinates $( a 1 , a 2 , ⋯ , a k )$ such that $a 1 + a 2 + ⋯ + a k = n$.
Ma Yuankui and Zhang Wenpeng [3] also studied this problem, and proved the following result:
$∑ a 1 + a 2 + ⋯ + a h + 1 = n F a 1 ( x ) F a 2 ( x ) ⋯ F a h + 1 ( x ) = 1 h ! · ∑ j = 1 h ( − 1 ) h − j · S ( h , j ) x 2 h − j × ∑ i = 0 n ( n − i + j ) ! ( n − i ) ! · 2 h + i − j − 1 i · ( − 1 ) i · 2 i · F n − i + j ( x ) x i ,$
where $S ( h , i )$ is defined by $S ( h , 0 ) = 0$, $S ( h , h ) = 1$, and
$S ( h + 1 , i + 1 ) = 2 · ( 2 h − 1 − i ) · S ( h , i + 1 ) + S ( h , i )$
for all positive integers $1 ≤ i ≤ h − 1$.
On the other hand, Zhang Yixue and Chen Zhuoyu [4] studied the properties of Chebyshov polynomials, and proved the following identity:
$∑ a 1 + a 2 + ⋯ + a h + 1 = n U a 1 ( x ) U a 2 ( x ) ⋯ U a h + 1 ( x ) = 1 2 h · h ! · ∑ j = 1 h C ( h , j ) x 2 h − j ∑ i = 0 n ( n − i + j ) ! ( n − i ) ! · 2 h + i − j − 1 i · U n − i + j ( x ) x i ,$
where $C ( h , i )$ is a second order non-linear recurrence sequence defined by $C ( h , 0 ) = 0$, $C ( h , h ) = 1$, $C ( h + 1 , 1 ) = 1 · 3 · 5 ⋯ ( 2 h − 1 ) = ( 2 h − 1 ) ! !$ and $C ( h + 1 , i + 1 ) = ( 2 h − 1 − i ) · C ( h , i + 1 ) + C ( h , i )$ for all $1 ≤ i ≤ h − 1$.
Many other papers related to Fibonacci numbers, Fibonacci polynomials, Chebyshov polynomials and second-order linear recurrence sequences can also be found in references [5,6,7,8,9,10,11,12,13,14,15,16,17,18], here we will no longer list them one by one.
After careful analysis of the research content in [1,2,3,4], we think it can be summarized as a sentence: That is, to study the symmetry sum problem of the generalized second-order linear recursive sequence. Of course, they are meaningful to study these problems. It not only reveals the profound properties of the generalized second-order linear recursive polynomials and sequences, but also greatly simplifies the calculation of the symmetry sums of these polynomials and sequences in practice.
Inspired by [1,2,3,4], in this paper, we will use a new method to study the computational problem of the symmetry sums of a certain second-order linear recurrence sequences, and give a simple and beautiful generalized conclusion. That is, we will use the elementary methods and the symmetry properties of the characteristic roots to prove the following results:
Theorem 1.
Let $S n = C 1 · S n − 1 + C 2 · S n − 2$ denotes any second-order linear recurrence sequence with $S 0 = 1$ and $S 1 = C 1$. Then we have the identity
$∑ a 1 + a 2 + ⋯ + a k = n S a 1 · S a 2 · S a 3 ⋯ S a k = 1 2 ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · ( − C 2 ) i · S n − 2 i + C 2 · S n − 2 − 2 i .$
It is clear that if we taking $C 1 = x$ and $C 2 = 1$, then from Theorem 1 we may immediately deduce the following:
Corollary 1.
For any positive integers n and k, we have the identity
$∑ a 1 + a 2 + ⋯ + a k = n F a 1 + 1 ( x ) · F a 2 + 1 ( x ) · F a 3 + 1 ( x ) ⋯ F a k + 1 ( x ) = 1 2 ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · ( − 1 ) i · F n + 1 − 2 i ( x ) + F n − 1 − 2 i ( x ) .$
Corollary 2.
For any positive integer m, n and k, we have the identity
$∑ a 1 + a 2 + ⋯ + a k = n U a 1 T m ( x ) · U a 2 T m ( x ) · U a 3 T m ( x ) ⋯ U a k T m ( x ) = ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · T m ( n − 2 i ) ( x )$
and
$∑ a 1 + a 2 + ⋯ + a k = n U a 1 x · U a 2 x · U a 3 x ⋯ U a k x = ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · x U n − 1 − 2 i ( x ) − U n − 2 − 2 i ( x ) .$
It is clear that our Corollary 1 and Corollary 2 are much easier than the results in [1,2,3,4]. If $S n + 2 = C 1 · S n + 1 + C 2 · S n$ with $S 0 = 1$ and $S 1 = C 1$ and $H n + 2 = D 1 · H n + 1 + D 2 · H n$ with $H 0 = 1$ and $H 1 = D 1$ are two different second-order linear recurrence sequences, such that the polynomials $x 2 − C 1 x − C 2$ and $x 2 − D 1 x − D 2$ co-prime. That is, $x 2 − C 1 x − C 2 , x 2 − D 1 x − D 2 = 1$. Then we define sequence ${ M n }$ as follows:
$M n = ∑ i = 0 n S i · H n − i n = 0 , 1 , 2 , ⋯ .$
For the sequence ${ M n }$ defined in (2), we have the following conclusion:
Theorem 2.
The sequence ${ M n }$ is a fourth-order linear recurrence sequence, and it satisfy the fourth-order linear recurrence formula
$M n + 4 = C 1 + D 1 M n + 3 + C 2 + D 2 + C 1 D 1 M n + 2 − C 1 D 2 + C 2 D 1 M n + 1 − C 2 D 2 M n , n ≥ 0 ,$
where $M 0 = 1$, $M 1 = C 1 + D 1$, $M 2 = C 1 2 + D 1 2 + C 2 + D 2 + C 1 D 1$ and
$M 3 = C 1 3 + D 1 3 + 2 C 1 C 2 + 2 D 1 D 2 + D 1 C 1 2 + C 2 + C 1 D 1 2 + D 2 .$
Taking $C 1 = x$, $C 2 = 1$, $D 1 = 2 x$ and $D 2 = − 1$, from our Theorem 2 we can deduce the following result:
Corollary 3.
For any integer $n ≥ 0$, we define the polynomials sequence
$M n ( x ) = ∑ i = 0 n F i + 1 ( x ) · U n − i ( x ) .$
Then $M n ( x )$ is a fourth-order linear recurrence polynomials, and it satisfy the recurrence formula
$M n + 4 ( x ) = 3 x M n + 3 ( x ) + 2 x 2 M n + 2 ( x ) − x M n + 1 ( x ) + M n ( x )$
for all integers $n ≥ 0$, where $M 0 ( x ) = 1$, $M 1 ( x ) = 3 x$, $M 2 ( x ) = 7 x 2$ and $M 3 ( x ) = 15 x 3 − x$, $F n ( x )$ and $U n ( x )$ denote the Fibonacci polynomials and Chebyshov polynomials of the second kind respectively.

## 2. Proof of the Theorem

In this section, we will prove our main results directly. First we prove Theorem 1.
Proof of Theorem 1.
It is clear that the characteristic equation of the sequence ${ S n }$ is $λ 2 − C 1 λ − C 2 = 0$. Let $α$ and $β$ are the two characteristic roots of the equation $λ 2 − C 1 λ − C 2 = 0$. Then we have
$S n = A α n + B β n with A + B = 1 and A α + B β = C 1 .$
That is,
$S n = A α n + B β n = α α − β · α n − β α − β · β n , n ≥ 0 .$
The generating function of the sequence ${ S n }$ is
$1 1 − C 1 x − C 2 x 2 = 1 ( 1 − α x ) ( 1 − β x ) = ∑ n = 0 ∞ S n · x n ,$
where $α · β = − C 2$ and $α + β = C 1$.
For any positive integer k, we have the identity
$1 1 − C 1 x − C 2 x 2 k = 1 ( 1 − α x ) k · ( 1 − β x ) k = ∑ n = 0 ∞ ∑ a 1 + a 2 + ⋯ + a k = n S a 1 · S a 2 · S a 3 ⋯ S a k · x n .$
On the other hand, from the properties of the power series we have
$1 ( 1 − x ) k = ∑ n = 0 ∞ n + k − 1 k − 1 · x n , | x | < 1 .$
Thus, from (5) and the properties of the power series we have
$1 ( 1 − α x ) k ( 1 − β x ) k = ∑ n = 0 ∞ n + k − 1 k − 1 α n x n ∑ n = 0 ∞ n + k − 1 k − 1 β n x n = ∑ n = 0 ∞ ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · α i · β n − i · x n .$
Combining (4), (6) and note that $α · β = − C 2$ and the symmetry of $α$ and $β$ we can deduce the identity
$∑ a 1 + a 2 + ⋯ + a k = n S a 1 · S a 2 · S a 3 ⋯ S a k = ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · α i · β n − i = ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · ( − C 2 ) i · β n − 2 i = ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · ( − C 2 ) i · α n − 2 i = ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · ( − C 2 ) i · 1 2 α n − 2 i + β n − 2 i .$
From the definitions A and B we have
$A · ( α − β ) = α and B · ( β − α ) = β .$
So for any integer r, from the definition of $S n$ we have
$α r + β r = α · α r − 1 + β · β r − 1 = A · ( α − β ) · α r − 1 + B · ( β − α ) · β r − 1 = A · α r + B · β r − α · β A · α r − 2 + B · β r − 2 = S r + C 2 · S r − 2 .$
Now combining (7) and (8) we may immediately deduce the identity
$∑ a 1 + a 2 + ⋯ + a k = n S a 1 · S a 2 · S a 3 ⋯ S a k = ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · α i · β n − i = 1 2 ∑ i = 0 n i + k − 1 k − 1 n − i + k − 1 k − 1 · ( − C 2 ) i · S 2 − 2 i + C 2 · S n − 2 − 2 i .$
This proves Theorem 1. □
Proof of Theorem 2.
Note that $x 2 − C 1 x − C 2 , x 2 − D 1 x − D 2 = 1$, so from the definitions of $α$, $β$, $δ$ and $γ$ we have
$1 − C 1 x − C 2 x 2 · 1 − D 1 x − D 2 x 2 = 1 − C 1 + D 1 x − C 2 + D 2 − C 1 D 1 x 2 + C 1 D 2 + C 2 D 1 x 3 + C 2 D 2 x 4 = ( 1 − α x ) ( 1 − β x ) ( 1 − δ x ) ( 1 − γ x ) ,$
where $α$, $β$, $δ$ and $γ$ are different each others.
It is clear that from the definitions sequences $S n$ and $H n$ we have
$1 1 − C 1 x − C 2 x 2 · 1 − D 1 x − D 2 x 2 = ∑ n = 0 ∞ ∑ i = 0 n S i · H n − i · x n .$
On the other hand, from the definition and properties of the fourth-order linear recurrence sequence we also have
$1 1 − C 1 x − C 2 x 2 · 1 − D 1 x − D 2 x 2 = 1 ( 1 − α x ) ( 1 − β x ) ( 1 − δ x ) ( 1 − γ x ) = ∑ n = 0 ∞ M n · x n ,$
where $M 0 = 1$, $M 1 = C 1 + D 1$, $M 2 = C 1 2 + D 1 2 C 2 + D 2 + C 1 D 1$,
$M 3 = C 1 3 + D 1 3 + 2 C 1 C 2 + 2 D 1 D 2 + D 1 D 1 2 + D 2 + C 1 D 1 2 + D 2$
and
$M n + 4 = C 1 + D 1 M n + 3 + C 2 + D 2 + C 1 D 1 M n + 2 − C 1 D 2 + C 2 D 1 M n + 1 − C 2 D 2 M n , n ≥ 0 .$
From (11) and (12) we know that the sequence
$M n = ∑ i = 0 n S i · H n − i$
is a fourth-order recurrence sequence, and it satisfy the recurrence Formula (12).
This completes the proof of Theorem 2. □

## Author Contributions

Writing—original draft: Y.L.; Writing—review and editing: X.L.

## Funding

This work is supported by the Xizang N. S. F. (XZ2017ZRG-65) and the N. S. F. (11771351) and (11826205) of China.

## Acknowledgments

The authors would like to thank the referees for their very helpful and detailed comments, which have significantly improved the presentation of this paper.

## Conflicts of Interest

The authors declare no conflict of interest.

## References

1. Zhang, W.P. Some identities involving the Fibonacci numbers and Lucas numbers. Fibonacci Q. 2004, 42, 149–154. [Google Scholar]
2. Yi, Y.; Zhang, W.P. Some identities involving the Fibonacci polynomials. Fibonacci Q. 2002, 40, 314–318. [Google Scholar]
3. Ma, Y.K.; Zhang, W.P. Some identities involving Fibonacci polynomials and Fibonacci numbers. Mathematics 2018, 6, 334. [Google Scholar] [CrossRef] [Green Version]
4. Zhang, Y.X.; Chen, Z.Y. A new identity involving the Chebyshev polynomials. Mathematics 2018, 6, 244. [Google Scholar] [CrossRef] [Green Version]
5. Ma, R.; Zhang, W.P. Several identities involving the Fibonacci numbers and Lucas numbers. Fibonacci Q. 2007, 45, 164–170. [Google Scholar]
6. Wang, S.Y. Some new identities of Chebyshev polynomials and their applications. Adv. Differ. Equ. 2015, 2015, 355. [Google Scholar]
7. Chen, L.; Zhang, W.P. Chebyshev polynomials and their some interesting applications. Adv. Differ. Equ. 2017, 2017, 303. [Google Scholar]
8. Li, X.X. Some identities involving Chebyshev polynomials. Math. Probl. Eng. 2015, 2015, 950695. [Google Scholar] [CrossRef]
9. Ma, Y.K.; Lv, X.X. Several identities involving the reciprocal sums of Chebyshev polynomials. Math. Probl. Eng. 2017, 2017, 4194579. [Google Scholar] [CrossRef] [Green Version]
10. Wang, T.T.; Zhang, H. Some identities involving the derivative of the first kind Chebyshev polynomials. Math. Probl. Eng. 2015, 2015, 146313. [Google Scholar] [CrossRef]
11. Zhang, W.P.; Wang, T.T. Two identities involving the integral of the first kind Chebyshev polynomials. Bull. Math. Soc. Sci. Math. Roum. 2017, 108, 91–98. [Google Scholar]
12. Chen, Z.Y.; Qi, L. Some convolution formulae related to the second-order linear recurrence sequence. Symmetry 2019, 11, 788. [Google Scholar] [CrossRef] [Green Version]
13. Kim, T.; Dolgy, D.V.; Kim, D.S. Representing sums of finite products of Chebyshev polynomials of the second kind and Fibonacci polynomials in terms of Chebyshev polynomials. Adv. Stud. Contemp. Math. 2018, 28, 321–336. [Google Scholar]
14. Kaygisiz, K.; Sahin, A. Determinantal and permanental representations of Fibonacci type numbers and polynomials. Rocky Mt. J. Math. 2016, 46, 227–242. [Google Scholar] [CrossRef]
15. Wu, Z.G.; Zhang, W.P. Several identities involving the Fibonacci polynomials and Lucas polynimials. J. Inequal. Appl. 2013, 2013, 205. [Google Scholar] [CrossRef] [Green Version]
16. Meng, Y.Y. A new identity involving balancing polynomials and balancing numbers. Symmetry 2019, 11, 1141. [Google Scholar] [CrossRef] [Green Version]
17. Kim, T.; Dolgy, D.; Kim, D.; Seo, J. Convolved Fibonacci numbers and their applications. ARS Comb. 2017, 135, 119–131. [Google Scholar]
18. Zhou, S.J.; Chen, L. Tribonacci numbers and some related interesting identities. Symmetry 2019, 11, 1195. [Google Scholar] [CrossRef] [Green Version]

## Share and Cite

MDPI and ACS Style

Liu, Y.; Lv, X. Some New Identities of Second Order Linear Recurrence Sequences. Symmetry 2019, 11, 1496. https://doi.org/10.3390/sym11121496

AMA Style

Liu Y, Lv X. Some New Identities of Second Order Linear Recurrence Sequences. Symmetry. 2019; 11(12):1496. https://doi.org/10.3390/sym11121496

Chicago/Turabian Style

Liu, Yanyan, and Xingxing Lv. 2019. "Some New Identities of Second Order Linear Recurrence Sequences" Symmetry 11, no. 12: 1496. https://doi.org/10.3390/sym11121496

Note that from the first issue of 2016, this journal uses article numbers instead of page numbers. See further details here.